2019
DOI: 10.3390/atmos10060308
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Modeled Exposure of Wildland Fire Smoke for Human Health Studies in California

Abstract: Wildland fire smoke exposure affects a broad proportion of the U.S. population and is increasing due to climate change, settlement patterns and fire seclusion. Significant public health questions surrounding its effects remain, including the impact on cardiovascular disease and maternal health. Using atmospheric chemical transport modeling, we examined general air quality with and without wildland fire smoke PM 2.5 . The 24-h average concentration of PM 2.5 from all sources in 12-km gridded output from all sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
(113 reference statements)
3
19
0
Order By: Relevance
“…PM 2.5 concentration estimates from chemical transport models have been shown to be an important input to machine learning models for PM 2.5 15 , 17 . We obtained daily estimates of PM 2.5 at 12 km spatial resolution from runs of the CMAQ (Community Multi-scale Air Quality) model from the U.S. EPA for the years 2008–2016, the years for which the CMAQ estimates are available 37 .…”
Section: Methodsmentioning
confidence: 99%
“…PM 2.5 concentration estimates from chemical transport models have been shown to be an important input to machine learning models for PM 2.5 15 , 17 . We obtained daily estimates of PM 2.5 at 12 km spatial resolution from runs of the CMAQ (Community Multi-scale Air Quality) model from the U.S. EPA for the years 2008–2016, the years for which the CMAQ estimates are available 37 .…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of research has demonstrated that ozone, a gas phase criteria pollutant in the U.S., can also be enhanced in the presence of wildfire smoke (Brey & Fischer, 2016;Jaffe et al, 2013;Lu et al, 2016;McClure & Jaffe, 2018a). The deteriorated air quality due to wildfire smoke can impact public health on large scales (Delfino et al, 2009;Fisk & Chan, 2017;Gan et al, 2017;Koman et al, 2019;Lipner et al, 2019;Rappold et al, 2011). Given this suite of impacts on air quality, alongside other impacts on people, property and economics, there is a need to understand 1) what drives yearto-year wildfire activity, 2) how those drivers may change in the future, and 3) how future burn area and total emissions may respond.…”
Section: Introductionmentioning
confidence: 99%
“…Population-level exposure to wildfire emissions is typically estimated using one or more primary datasets: monitoring station observations, chemical transport models (CTMs), and satellite-based measurements 15,16 . Each dataset has strengths and weaknesses for estimating wildfire PM2.5 concentrations.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%